2019
DOI: 10.1088/1361-6439/ab4b7f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of stress on metal surfaces by laser-induced breakdown spectroscopy

Abstract: In this study, we evaluated the feasibility of using laser-induced breakdown spectroscopy (LIBS) to determine the stress generated in metal materials by comparing measured stress levels with those determined by x-ray diffraction (XRD). Magnesium (Mg) alloy specimens underwent impact stress generated under ultrasonic peening. Stainless steel specimens were subjected to bending stress. The reference stress for each specimen was measured using XRD. LIBS measurements were performed to determine the correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Rusak et al 10 investigated the change in the Ca/F signal ratio at different depths of the archaeological bones, and found that the signal ratio could be used to distinguish the degree of preservation of the bones. Kang et al 11 analyzed the stress distribution in metals using the ratio of ionic to atomic spectral line intensity and confirmed the potential of using LIBS to measure stress in metals.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Rusak et al 10 investigated the change in the Ca/F signal ratio at different depths of the archaeological bones, and found that the signal ratio could be used to distinguish the degree of preservation of the bones. Kang et al 11 analyzed the stress distribution in metals using the ratio of ionic to atomic spectral line intensity and confirmed the potential of using LIBS to measure stress in metals.…”
Section: Introductionmentioning
confidence: 90%
“…However, for the actual spectral data value 𝑦 π‘βˆ’1 is not equal to 𝑦 𝑐+1 in most cases, it is difficult for 𝑦 π‘βˆ’1 and 𝑦 𝑐+1 to satisfy the ideal fitting profile distribution when π‘₯ 𝑐 is constant. For this reason, by taking (π‘₯ π‘βˆ’1 , 𝑦 π‘βˆ’1 ) and (π‘₯ 𝑐+1 , 𝑦 𝑐+1 ) into Equation (11) respectively with π‘₯ 𝑐 as the central wavelength of the spectral line, there will be two Lorentzian fitting profile with peak areas noted as 𝐴 1 and 𝐴 2 . Then the average area 𝐴 0 of 𝐴 1 and 𝐴 2 can be taken as the area of the ideal Lorentzian fitting, which can make the closest match to 𝑦 π‘βˆ’1 and 𝑦 𝑐+1 .…”
Section: Correction Of Handheld Libs Signalmentioning
confidence: 99%
“…An interesting application was proposed by Kang et al who discussed the use of LIBS for the evaluation of stress on the surfaces of a magnesium alloy and a steel plate . 46 Stress was induced to the magnesium alloy by ultrasonic peening, whereas bending was used to stress the steel plate. The ion to atom line intensity ratios were used as the basis of the analysis, with Mg being the analyte in the magnesium alloy and Cr being used for the steel sample.…”
Section: Metalsmentioning
confidence: 99%
“…Plasma generated through laser ablation of the material surface may include, not only chemical information of the material, but also physical information of the material surface. For example, the possibility of analyzing the physical properties of the surface of the material has been reported based on the characteristic that the spectral signal of plasma appears different depending on the stress, hardness, and roughness of the material [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%